An Investigation of Co-teaching to Improve Academic Achievement of Students with Disabilities: A Meta-analysis - Losinski, Mickey; Sanders, Sara; Parks-Ennis, Robin; Wiseman, Nicole; Nelson, Jessica; Katsiyannis, Antonis (Journal of the American Academy of Special Education Professionals, 2019)
Co-teaching is a popular means to support students with disabilities in the general education classroom. However, despite its widespread use, there are no meta-analyses examining the effects of co-teaching on academic outcomes for secondary students that analyze both study quality (e.g., the Council for Exceptional Children’s "Standards for Evidence-Based Practices in Special Education") and effects. We addressed both of these gaps in the current review, identifying nine articles (10 experimental studies) that were analyzed for quality and effects. No studies met all of the quality indicators and study effects showed no significant impact on students’ academic outcomes. Limitations and directions for research are presented. Implications for practice are also discussed, including the consideration that null effects, in this instance, do not necessarily suggest that co-teaching is ineffective.